2017
DOI: 10.5114/pdia.2016.61630
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance, diabetes mellitus and thyroid dysfunction in patients with palmoplantar pustulosis: a case-controlled study

Abstract: IntroductionPalmoplantar pustulosis (PPP) is a chronic pustular inflammatory skin disease; however, its pathogenesis is not well understood. Several factors, such as genetics, tobacco use and autoimmune issues, may contribute to this disease.AimThis research was conducted to investigate the relationships between insulin resistance, thyroid disease and PPP.Material and methodsThirty-three patients with PPP and 27 age- and gender-matched controls were analysed for their smoking histories, thyroid function tests,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In many studies, T2DM was observed in 7.7-19% of patients [2,7,9,25]. However, Ataş and Gönül [24] showed no significant difference between the fasting glucose, insulin, and homeostatic model assessment between a group with PPP and controls. The incidence of hyperlipidemia in patients with PPP ranges from 10.2-49% in different populations [2,5,25,26] and is a risk factor for ischemic heart disease and hypertension.…”
Section: Metabolic Syndromementioning
confidence: 94%
“…In many studies, T2DM was observed in 7.7-19% of patients [2,7,9,25]. However, Ataş and Gönül [24] showed no significant difference between the fasting glucose, insulin, and homeostatic model assessment between a group with PPP and controls. The incidence of hyperlipidemia in patients with PPP ranges from 10.2-49% in different populations [2,5,25,26] and is a risk factor for ischemic heart disease and hypertension.…”
Section: Metabolic Syndromementioning
confidence: 94%
“…Female sex is a predictive risk factor with an 8.8-fold higher risk for PPP (OR 141.7, p<0.0001). 16 , 18 Smoking is another risk factor with a 32.7-fold increased risk for the development of PPP (OR 147.6, p=0.006). 7 , 16 , 18 , 19 Smokers were 43–95.23% of the cohorts, and higher package-years and a longer period of smoking were associated with higher risk.…”
Section: Resultsmentioning
confidence: 99%
“… 16 , 18 Smoking is another risk factor with a 32.7-fold increased risk for the development of PPP (OR 147.6, p=0.006). 7 , 16 , 18 , 19 Smokers were 43–95.23% of the cohorts, and higher package-years and a longer period of smoking were associated with higher risk. 7 , 16 , 18 , 19 Smokers were significantly more prevalent in the PPP cohort than the PV cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Autoimmune thyroid disease is often observed in PPP patients. 7 Obesity (BMI > 25 mg/m2), T2DM, hyperlipidemia, allergic diseases (such as asthma, atopic dermatitis, and rhinitis allergica) and joint pain frequently accompanies PPP lesions. 7,8 PPP is challenging to treat and usually requires prolonged management.…”
Section: Introductionmentioning
confidence: 99%
“…7 Obesity (BMI > 25 mg/m2), T2DM, hyperlipidemia, allergic diseases (such as asthma, atopic dermatitis, and rhinitis allergica) and joint pain frequently accompanies PPP lesions. 7,8 PPP is challenging to treat and usually requires prolonged management. Therapy resistance and frequent relapse discourage patients from follow-up.…”
Section: Introductionmentioning
confidence: 99%